(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the current state and processes of copyright protection in Uzbekistan, in particular, the role of organizations that manage property rights on a collective basis. It is known that in accordance with the Law of the Republic of Uzbekistan “On Copyright and Related Rights”, authors, performers, producers of phonograms or other copyright holders of works of science, literature and art, in order to exercise their property rights, have the right to create organizations that manage their property rights on a collective basis. The article highlights the legal significance of the legal methods and means used by such organizations in the performance of their tasks and functions. Due to the fact that organizations that manage property rights on a collective basis are entitled to take any legal actions necessary to protect the rights they manage, the legal nature of these actions, the mechanisms for protecting the property and personal non-property rights of authors and right holders with highlights. The article also provides that an organization that manages property rights on a collective basis may agree with users on the amount of remuneration to be paid on behalf of the right holders and on the basis of the powers arising from them, and other terms of contracts. y Issues such as entering into agreements with users and negotiating with users the amount of remuneration for exercising the rights managed by the organization were also discussed. The conclusion is based on the issue of improving the “institution” of collective copyright management in Uzbekistan.